Decreased GABA-A Receptor Binding in Association With β-Lactam Antibiotic Use. - Flaus,A; Riaño,Barros DA; Hinz,R; Myers,JF; Lingford-Hughes,A; Koepp,MJ; Hammers,A; McGinnity,CJ (Clin Nucl Med, 2019)
β-Lactam antibiotics are proconvulsive. In laboratory animals, this effect seems to be predominantly mediated through inhibition of GABA-A receptors, but it has not been demonstrated in humans in vivo. We report images of a [C]Ro15-4513 PET from a 40-year-old man who had completed a 1-week course of flucloxacillin before it. Relative to healthy controls, the participant had significantly lower mean gray matter binding. These novel data suggest that, in humans, the proconvulsive effect of β-lactam antibiotics is mediated via either competition for the same benzodiazepine-binding site as [C]Ro15-4513 or downregulation of GABA-A receptor expression.